2022
DOI: 10.1115/1.4054400
|View full text |Cite
|
Sign up to set email alerts
|

Study on Anti-Scuffing Load-Bearing Thermoelastic Lubricating Properties of Meshing Gears With Contact Interface Micro-Texture Morphology

Abstract: In the process of gear meshing, it is an inevitable trend to encounter failure cases such as contact friction thermal behavior and interface thermoelastic scuffing wear. As one of the core influencing factors, the gear meshing contact interface micro-texture (CIMT) significantly restricts the gear transmission system (GTS) dynamic characteristics. This subject intends to the contact characteristic model and interface friction dynamics coupling model of meshing gear pair with different CIMT. Considering the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Pei et al [8] investigated the effect of micro surface texture on the performance of floating ring bearings using a multiscale finite element method and showed that the convex texture had a more significant effect on the bearing performance than the concave texture, and that the surface texture could increase the local pressure distribution and side leakage, thus reducing the temperature rise of the film. Ruan et al [9] studied gear meshing with consideration of the influence of the contact interface of micro-texture and frictional thermal load; it was found that the influence of the micro-texture on gear dynamic response was extremely restricted by the transient contact regularity of the meshing gear surface.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [8] investigated the effect of micro surface texture on the performance of floating ring bearings using a multiscale finite element method and showed that the convex texture had a more significant effect on the bearing performance than the concave texture, and that the surface texture could increase the local pressure distribution and side leakage, thus reducing the temperature rise of the film. Ruan et al [9] studied gear meshing with consideration of the influence of the contact interface of micro-texture and frictional thermal load; it was found that the influence of the micro-texture on gear dynamic response was extremely restricted by the transient contact regularity of the meshing gear surface.…”
Section: Introductionmentioning
confidence: 99%
“…These publications commonly RESEARCH note that the ability of dimples to provide the LCC has a strong influence on the lubrication characteristics. Since the pioneering works by Etsion et al [6], texturing has attracted attention for improving the lubrication performance of machine elements [7][8][9][10][11][12][13][14]. Many researchers attempted to provide optimal designs for fully and partially textured bearings in analysis based on the Reynolds equation or the Navier-Stokes equation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the accessorial density of grain boundaries facilitated the formation of strong atomic bonds at the material interface, reducing the possibility of intergranular fracture and enhancing the scuffing resistance. Wang et al[41] and Ruan et al[42] emphasized the critical impact of the microstructure of the contact zone on the tribological behavior and scuffing load carrying capacity of gears. As shown in figure20(c), the rough surface of DLSM-TD gears provided more opportunities for contact points to interact.…”
mentioning
confidence: 99%